The Complement System in Metabolic-Associated Kidney Diseases - Xu, Ziyu; Tao, Li; Su, Hua (Frontiers in Immunology, 2022)
Metabolic syndrome (MS) is a group of clinical abnormalities characterized by central or abdominal obesity, hypertension, hyperuricemia, and metabolic disorders of glucose or lipid. Currently, the prevalence of MS is estimated about 25% in general population and is progressively increasing, which has become a challenging public health burden. Long-term metabolic disorders can activate the immune system and trigger a low-grade chronic inflammation named "metaflammation". As an important organ involved in metabolism, the kidney is inevitably attacked by immunity disequilibrium and "metaflammation". Recently, accumulating studies have suggested that the complement system, the most important and fundamental component of innate immune responses, is actively involved in the development of metabolic kidney diseases. In this review, we updated and summarized the different pathways through which the complement system is activated in a series of metabolic disturbances and the mechanisms how complement mediate immune cell activation and infiltration, renal parenchymal cell damage, and the deterioration of renal function, providing potential new biomarkers and therapeutic options for metabolic kidney diseases.